Determination of generators' contributions to loads in pool based power system using Least Squares Support Vector Machine - M. W., Mustafa; M. H., Sulaiman; H., Shareef; S. N., Abd. Khalid (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/